2020
DOI: 10.1002/1873-3468.13949
|View full text |Cite
|
Sign up to set email alerts
|

Crowding tunes the organization and mechanics of actin bundles formed by crosslinking proteins

Abstract: Fascin and α‐actinin form higher‐ordered actin bundles that mediate numerous cellular processes including cell morphogenesis and movement. While it is understood crosslinked bundle formation occurs in crowded cytoplasm, how crowding affects the bundling activities of the two crosslinking proteins is not known. Here, we demonstrate how solution crowding modulates the organization and mechanical properties of fascin‐ and α‐actinin‐induced bundles, utilizing total internal reflection fluorescence and atomic force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 88 publications
(154 reference statements)
0
6
0
Order By: Relevance
“…The organization of the filaments (Gov, 2008) and the thickness of bundles (Lieleg et al, 2007) could be key factors in determining bundle nanomechanics-for example, actin bundles induced by depletion interactions were shown to increase in thickness as well as elastic modulus with an increase in the concentrations of PEG (Tharmann et al, 2006). A recent study has shown that crowding can tune the diameter of actin bundles crosslinked by actin binding proteins and possibly impact filament spacing (Park et al, 2021). Divalent cations were previously shown to alter the interfilament distance in bundles, with the greatest filament spacing at ∼7 nm for 30 mM Mg 2+ (Castaneda et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The organization of the filaments (Gov, 2008) and the thickness of bundles (Lieleg et al, 2007) could be key factors in determining bundle nanomechanics-for example, actin bundles induced by depletion interactions were shown to increase in thickness as well as elastic modulus with an increase in the concentrations of PEG (Tharmann et al, 2006). A recent study has shown that crowding can tune the diameter of actin bundles crosslinked by actin binding proteins and possibly impact filament spacing (Park et al, 2021). Divalent cations were previously shown to alter the interfilament distance in bundles, with the greatest filament spacing at ∼7 nm for 30 mM Mg 2+ (Castaneda et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In a living cell, actin bundles induced by ABPs are formed in a crowded cytoplasm; therefore, it is important to understand how crowding modulates ABP-induced bundling. Changes in filament bending stiffness and conformations in crowded environments [ 39 ] can influence interactions between filaments and ABPs, including actin-crosslinking proteins (e.g., fascin and α-actinin) [ 9 ] and severing proteins (e.g., gelsolin) [ 65 ]. Crowders with different sizes and concentrations [PEG and methylcellulose (MC)] have been shown to affect the organization patterns and potentially nucleation/growth of microtubule bundles crosslinked with microtubule-associated protein (MAP65) [ 66 ].…”
Section: The Influence Of Crowding and Cation Interactions On The Organization And Mechanics Of Actin Bundles Crosslinked By Actin-bindinmentioning
confidence: 99%
“…Crowders with different sizes and concentrations [PEG and methylcellulose (MC)] have been shown to affect the organization patterns and potentially nucleation/growth of microtubule bundles crosslinked with microtubule-associated protein (MAP65) [ 66 ]. Potential competitive interactions between crowding (PEG, sucrose, and Ficoll) and actin-crosslinking proteins, fascin, and α-actinin, have recently begun to be explored [ 9 ]. Macromolecular crowding influences the organization of either fascin or α-actinin bundles by reducing binding interactions between actin filaments and crosslinking proteins ( Figure 1C and Table 1 ), evidenced by fluorescence microscopy and atomic force microscopy imaging along with MD simulations [ 9 ].…”
Section: The Influence Of Crowding and Cation Interactions On The Organization And Mechanics Of Actin Bundles Crosslinked By Actin-bindinmentioning
confidence: 99%
See 2 more Smart Citations